Glucose Starvation-Induced Rapid Death of Nrf1α-Deficient, but Not Nrf2-Deficient, Hepatoma Cells Results from Its Fatal Defects in the Redox Metabolism Reprogramming. (28th July 2020) - Zhu, Yu-ping; Zheng, Ze; Xiang, Yuancai; Zhang, Yiguo
Abstract : Metabolic reprogramming exists in a variety of cancer cells, with the most relevance to glucose as a source of energy and carbon for survival and proliferation. Of note, Nrf1 was shown to be essential for regulating glycolysis pathway, but it is unknown whether it plays a role in cancer metabolic reprogramming, particularly in response to glucose starvation. Herein, we discover that Nrf1α -/- hepatoma cells are sensitive to rapid death induced by glucose deprivation, such cell death appears to be rescued by Nrf2 interference, but HepG2 (wild-type, WT ) or Nrf2 -/- cells are roughly unaffected by glucose starvation. Further evidence revealed that Nrf1α -/- cell death is resulted from severe oxidative stress arising from aberrant redox metabolism. Strikingly, altered gluconeogenesis pathway was aggravated by glucose starvation of Nrf1α -/- cells, as also accompanied by weakened pentose phosphate pathway, dysfunction of serine-to-glutathione synthesis, and accumulation of reactive oxygen species (ROS) and damages, such that the intracellular GSH and NADPH were exhausted. These demonstrate that glucose starvation leads to acute death of Nrf1α -/-, rather than Nrf2 -/-, cells resulting from its fatal defects in the redox metabolism reprogramming. This is owing to distinct requirements of Nrf1 and Nrf2 for regulating the constructive and inducible expression of key genes involved in redox metabolic reprogramming by glucose deprivation. Altogether, this work substantiates the preventive and therapeutic strategies against Nrf1α -deficient cancer by limiting its glucose and energy demands.